A Novel Method of Immobilizing Antigens on Gold Electrode for Immunosensing - Uyen, Nguyen Hoang Phuong; Nenad, Gajovic-Eichelmann; Bier, Frank. F.; Thanh, Ngo Vo Ke (Communications in Physics, 2015)
An antigen modified gold electrode based on a self-assembled lipoic acid monolayer has been developed. The contact angle measurement and cyclic voltammetry confirm the formation of a dense self-assembled monolayer on gold from 100 mM lipoic acid in ethanol. The electrochemical behavior shows a stable activity in a range of potential from -0.2 V to 0.65 V vs. Ag/AgCl. By applying a potential of 1 V vs. Ag/AgCl the monolayer is completely removed by oxidative desorption and a clean gold surface re-established. This allows for an easy renewal of the gold surface and recycling of modified immunosensor chips. This lipoic acid monolayer was covalently functionalized with a small molecule antigen synthesized from progesterone-3-(O-carboxymethyl)oxime and 4,7,10-trioxa-1,13 tridecanediamine to form a well ordered, low unspecific binding, antigen layer for an antibody-antigen interaction study.The effectiveness of antigen - antibody binding reaction was demonstrated by fluorescence imaging using a fluorescence-labeled anti-progesterone antibody as the binding partner. The new approach represents a way of improving the surface chemistry of electrochemical, surface-plasmon resonance and QCM-based immunosensors for which reusability, simplicity and sensitivity in flow-injection mode are required